PEMBENTUKAN BADAN RISET DAN INOVASI NASIONAL SEBAGAI UPAYA MENUJU GOOD GOVERNANCE DENGAN PRINSIP REFORMASI BIROKRASI - Nurul Jannah Lailatul Fitria (P3M STISIPOL Dharma Wacana Metro, 2021)
The Indonesian government shows its seriousness in Bureaucratic Reform which aims to create a good governance bureaucracy. One of the actions taken by the government is to merge the Ministry of Research and Technology with the Ministry of Education and Culture, to become the National Research and Innovation Agency (BRIN) to develop structured research, innovation and technology. The research method used in writing this article is a literature review method from various sources related to the object of research. This research is a descriptive qualitative research. So it can be seen that the existence of BRIN is part of the reform strategy towards good governance with a system of change and organizational development. The form of organizational change is realized by LIPI, BATAN, BPPT, LAPAN merging into BRIN. So that the implementation of research and budget will focus on one institution. The concept of change and development in BRIN will shape the quality of research in Indonesia for the better. The focus of BRIN's activities is on integrated research, development, assessment, application, invention and innovation. Then science and technology can be mastered faster.